2019
DOI: 10.1007/s11033-019-04993-3
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the relationship between the expression of CCR7/CCL19 axis and selected regulatory miRNAs in non-small cell lung cancer

Abstract: CC chemokine receptor type 7 (CCR7) and its ligands has been implicated in the occurrence and progression of NSCLC. Previous studies have revealed that the diagnostic value of CCR7/CCL19 axis in lung tumorigenesis remains controversial. The present study evaluates the relationship between the mRNA expression of CCR7/CCL19 axis and selected regulatory miRNAs in NSCLC patients. It analyzes the expression level of CCR7 mRNA and its ligand in tumor tissue in relation to expression level of two miRNAs: miR let-7a a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…This research is a continuation and extension of our earlier study, the aim of which was to evaluate changes in the expression level of CCR7 and CCL19 in tumor tissue and of two regulatory miRNAs of these genes (miR let-7a and miR-335) in serum exosomes [16]. A particularly valuable element of this study is the measurement of miRNA expression level in tumor tissue.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This research is a continuation and extension of our earlier study, the aim of which was to evaluate changes in the expression level of CCR7 and CCL19 in tumor tissue and of two regulatory miRNAs of these genes (miR let-7a and miR-335) in serum exosomes [16]. A particularly valuable element of this study is the measurement of miRNA expression level in tumor tissue.…”
Section: Introductionmentioning
confidence: 90%
“…The biological material was secured and prepared according to the protocol described in the previous article [16]. Isolation of total RNA from tissue and exosomes was performed with the same type of isolation kits as before.…”
Section: Tissue and Serum Collectionmentioning
confidence: 99%
“…In NSCLC, a study observed an upregulation of CXCL9/CCR7 in tumor tissue, especially in patients with metastasis to lymph nodes. Intriguingly, the expression of CXCL9/CCR7 were associated with two miRNAs: let-7a and miR-335 (57). In addition, high expression of CXCL9 was observed in melanoma-derived cancer stem cells (CSC), which may accelerate efficient recognition and kill by NK cells (58).…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis between the expression of CCL19 and the survival of patients or TICs in TIME suggested that CCL19 was not only signi cantly associated with the survival and clinicpathological characteristics of BC patients, but also participated in the regulation of TIME partly through closely communicating with multiple TICs, including macrophages, T cells, B cells, NK cells, DCs, mast cells and neutrophils. Previous studies indicated that CCL19 greatly participated in cancer cell proliferation, angiogenesis, migration, invasion and immune cell in ltration [23] in multiple cancers, including gastric cancer [29] , colorectal cancer [30] , non-small cell lung cancer [31,32] , lymphoma [33] and melanoma [13] . These biological functions of CCL19 were involved in the activation of CCR7/absent in melanoma 2 (AIM2) signaling pathway [29] , interaction with miRNAs [30] , the migration and maturation of DC [34] and migration of NK cells [35] .…”
Section: Discussionmentioning
confidence: 99%